2021
DOI: 10.47709/ijeal.v1i3.1241
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Expectation of EFL Students on Ideal Online Learning: A Survey Study in an Indonesian Islamic Higher Education

Abstract: The present study is aimed to investigate EFL students’ perception on the use of Google Classroom as an online learning platform and their expectation on an ideal online learning. 112 EFL students at State Islamic University of Mataram responded the survey study which was designed with open-ended questions. Students’ responses were qualitatively analyzed to find the main themes and sub-themes. The finding reveals that most students, 67%, perceived the use of Google classroom negatively due to the potential pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In the interview they also explained that blended learning with LMS made it easier for them to complete their assignments due to its ease of use and other benefits such as being a replacement platform in a critical era making it easier for those who live far from campus. This finding is in line with a study by Ariawan (2021 andLu et al,(2012) who found that the EFL students tend to address the ease of use and its flexibility. This leads them to positively perceive the use of LMS.…”
Section: P6supporting
confidence: 92%
See 1 more Smart Citation
“…In the interview they also explained that blended learning with LMS made it easier for them to complete their assignments due to its ease of use and other benefits such as being a replacement platform in a critical era making it easier for those who live far from campus. This finding is in line with a study by Ariawan (2021 andLu et al,(2012) who found that the EFL students tend to address the ease of use and its flexibility. This leads them to positively perceive the use of LMS.…”
Section: P6supporting
confidence: 92%
“…Blended learning blends the traditional classroom with the online learning model. It provides learners with an efficient and effective educational experience, as well as the extra benefit of increased flexibility (Ariawan, 2021). It means that students are able to access the learning remotely from home without physically attend the class.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, speaking, listening, reading, and writing are the four skills that students should be proficient in when learning English. Besides, when English learning process, EFL students also use a variety of platforms for their online coursework, including WhatsApp, Google Translate, Edmodo, Google Classroom, and learning management systems (LMS) (Ariawan, 2021;Famularsih, 2020;Hendrawaty et al, 2021;Manurung et al, 2020;Saroh & Arifmiboy, 2022;Wirantaka & Fijanah, 2022).…”
Section: Online Learning In Efl Contextmentioning
confidence: 99%
“…Through regular meetings and discussions with mentors, student teachers are encouraged to reflect on their teaching practices, critically analyze their strengths and areas for improvement, and set goals for their professional development. This reflective process enhances their ability to make informed decisions and continuously improve their teaching methods (Ariawan, 2021;Damayanti et al, 2023). Mentors can provide valuable feedback and guide student teachers in self-assessment, helping them identify areas of growth and providing suggestions for further development including comprehensive understanding and skill to interact with school members and to get insight about students' behaviour (Tanjung et al, 2021).…”
Section: Introductionmentioning
confidence: 99%